Polarisasi Spiritualitas Ummat Islam di Era Pandemi Covid-19 - Sirajun Nasihin (AS-SABIQUN, 2021)
This paper aims to present the results of an analysis of the phenomenon of religious communities, especially Muslims in the Covid-19 pandemic era which shows various patterns of spirituality. This paper is a review of the attitude patterns that appear to the surface, not providing justification or criticism of the attitudes of each pattern that appears. The methodology used is phenomenological analysis on social media which is currently emerging with various presentations. The author sees it from the point of view of epistemology proposed by a modern Muslim philosopher Muhammad Abid al-Jabiri who suggests three kinds of reasoning that humans have taken throughout the ages to produce their knowledge, namely bayani, irfani, and burhani reasoning. The religious phenomenon of the Muslim community in this pandemic era is the embodiment of its scientific system so that it will automatically show which epistemology is the basis for understanding the teachings of Islam. The conclusion of this analysis is that Muslims are divided into several attitudes of spirituality in response to government policies, namely; 1) intolerant (counter-active) attitude towards government policies based on their religious understanding, 2) tolerant attitude (pro-active) and providing support to the government based on their understanding and 3) indifferent attitude towards government policies.